Estimating Fuelwood Demand and Supply for Forest User Groups from Community Forests - Aryal, Suman; Pokharel, Govinda Raj; Kafle, Narayan Prasad; Gaire, Narayan Prasad (Nepal Journal of Science and Technology, 2010)
Main objectives of this study were to estimate annual fuelwood demand in Community Forest Users Group (CFUG), and annual sustainable supply of the same from Community Forest (CF). Study was done each one community forest of Terai and Hills; Shanti Community Forest (SCF), Saljhandi, Rupandehi (Terai) and Barangdikol Community Forest (BCF), Madanpokhara, Palpa (Hill), in Western Development region, Nepal. Extensive field work was carried out from May to July, 2007. Sustainable supply of fuelwood from the CF was estimated by using the methodology mentioned in the "Revised guidelines for community forest resource inventory", MoFSC, 2004. Stratified random sampling with proportional allocation method in three households (HHs) type; HHs with biogas, HHs with ICS and HHs without biogas & ICS, was used to cover 15 % of the HHs in the CFUG during HHs survey for the estimation of fuelwood demand. The fuelwood consumption pattern in these three HHs types was compared. The result showed that SCF was found in good condition where as BCF was in poor condition based on regeneration rate and growing stock. Demand and supply analysis showed that only 12.03% of fuelwood demand in SCFUG and 8.03% of the fuelwood demand in the BCFUG was fulfilled by the sustainable supply of fuelwood from the CF. Key-words: Biogas; Consumption; Energy; Improved cooking stove; Growing stock DOI: 10.3126/njst.v10i0.2948 <!–[if gte mso 10]> <![endif]–> Nepal Journal of Science and Technology Vol. 10, 2009 Page:129-133